Distribution and Sources of Eco-toxic Metals in Particulate, Colloid, Dissolved Fraction and Sediment in the Miri Estuary (Sarawak) - William, Fiona Bassy (Curtin University, 2023)
This research aims to study the distribution and sources of ecotoxic metals in different size fractions in the Miri Estuary. Samples (water and sediment) were collected and analysed for physical parameters, major ions, metals, nutrients and isotopes. Elemental concentration increased from upstream to downstream of the river. Metal distribution showed increasing concentrations from colloidal to particulate fractions. Colloidal fractions significantly contributing to the contaminant transport in the upstream and midstream.